Effect of Annealing on Innovative CsPbI3-QDs Doped Perovskite Thin Films - Pao-Hsun Huang; Yu-Hao Chen; Shui-Yang Lien; Kuan-Wei Lee; Na-Fu Wang; Chien-Jung Huang (Crystals, 2021)
In this study, a simple hot-injection method to synthesize high-quality inorganic perovskite cesium lead iodide (CsPbI3) quantum-dots (QDs) was demonstrated. Adding CsPbI3 QDs into the organic perovskite methylamine lead triiodide (CH3NH3PbI3) to form a composite perovskite film, annealed by different temperatures, was found to be effectively enhanced by the perovskite crystallization. The intensity of the preferred peak (110) of MAPbI3 was enhanced by increasing the size of the crystal and reducing the cluster crystal. The densest film can be found at annealing temperature of 140 °C. The full width half maximum of MAPbI3 and CsPbI3 was analyzed through XRD peak fitting. This was a huge breakthrough for QDs doped perovskite films.